2017
DOI: 10.1016/j.jnucmat.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Angular and velocity distributions of tungsten sputtered by low energy argon ions

Abstract: Sputtering by ions with low near-threshold energies is investigated. Experiments and simulations are conducted for tungsten sputtering by low-energy, 85-200 eV Ar atoms. The angular distributions of sputtered particles are measured. A new method for molecular dynamics simulation of sputtering taking into account random crystallographic surface orientation is developed, and applied for the case under consideration. The simulations approximate experimental results well. At low energies the distributions acquire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…When these atoms are W, it was shown that their energy distribution function (EDF) established with Thompson model 55 is consistent with the EDF found with molecular dynamic simulations by taking incident energies of 150 -200 eV for Ar + . 56 In this energy range close to our conditions, the EDF maximum of sputtered atoms at the cathode surface given by Thompson model is around half of W binding energy (Eb = 8.9 eV) and their mean energy is near 12 eV.…”
Section: Laser Induced Fluorescence Measurementssupporting
confidence: 78%
“…When these atoms are W, it was shown that their energy distribution function (EDF) established with Thompson model 55 is consistent with the EDF found with molecular dynamic simulations by taking incident energies of 150 -200 eV for Ar + . 56 In this energy range close to our conditions, the EDF maximum of sputtered atoms at the cathode surface given by Thompson model is around half of W binding energy (Eb = 8.9 eV) and their mean energy is near 12 eV.…”
Section: Laser Induced Fluorescence Measurementssupporting
confidence: 78%
“…where Z is the atomic number of the target material, E b the binding energy in eV, M 1 and M 2 masses for bombarding (M 1 ) and target (M 2 ) atoms. As the remaining parameters (A, B and m) were not given explicitly by the authors, we have fitted them on the angular distributions provided by the authors [23][24][25]. The polynomial fits obtained agree well with the experimental and numerical results reported by several sources [23,[25][26][27].…”
Section: Angular Dependencesupporting
confidence: 60%
“…It has been reported consistently in various sources that in this energy range the emitted particles have a butterfly-like spatial distribution [23][24][25]. This has to be taken into account in this study, as it will affect the velocity distribution function of W atoms along the observation direction.…”
Section: Angular Dependencementioning
confidence: 96%
“…In the simulations, the cosine angular distribution for the sputtered particles was assumed. While this type of distribution was theoretically predicted in large cascade approximation [27], if the energy of sputtered particles is not high enough, the real angular distribution of the sputtered particles may differ from the cosine one [28]. Nevertheless, the slight variations of the angular distribution do not affect significantly the deposition profiles.…”
Section: Experimental Setup and Code Validationmentioning
confidence: 78%